Evaluation of Coupling Coordination among the Urban Physical Environment, Economy, and Population: A Case Study of 36 Main Cities in China - Min Chen; Zhihao Sun; Yuanjie Wang; Shuaifeng Guo (Advances in Civil Engineering)
In the past three decades, about 0.93% of people moved from rural areas to cities per year in China. Therefore, understanding of the relationships among urban physical environment (UPE), economic development, and population growth are significant for China to realize sustainable urban development. Based on the concept and connotation of UPE and ecocity, the UPE evaluation system was constructed containing 6 first-level of indicators (i.e., climate, quality of ambient air and atmosphere, freshwater, wastewater, built environment, and noise pollution) and 13 second-level indicators. An entropy weight-TOPSIS model was developed in order to evaluate the UPE system, using the data of China’s 36 main cities from 2003 to 2016. The coupling coordination degree (CCD) among the UPE, economy, and population was measured by a ternary CCD model. The results showed that (1) the UPE of 36 main cities showed periodic fluctuations throughout the 14 years, and the coastal cities and southern cities had superior UPE than the inland cities and northern cities, respectively; (2) the vast majority of cities’ CCD had experienced steady upward trends. UPE, economy, and population promoted mutually in most of the cities, but in a few super cities, the economic development and population growth exceeded the capacity of UPE. Meanwhile, the CCD gaps between the northern and southern cities were significantly widened.